Jahresbericht 2006 : Die vorteile der weltwirtschaft fur alle sichern. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The Annual Report 2006 to the Board of Governors reviews the IMF's activities and policies during the financial year (May 1, 2005, through April 30, 2006). The main sections cover the Fund's Medium-Term Strategy; country, global, and regional surveillance; strengthening surveillance and crisis prevention; IMF program support and crisis resolution; the Fund's role in low-income countries; technical assistance and training; financial operations and policies; and governance and management of the IMF. Besides the full financial statements for the year, appendixes cover international reserves, financial operations and transactions, principal policy decisions, press communiques of advisory committees, Executive Directors and their voting power, and changes in the Executive Board's membership.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet